Operação meio ambiente - Faquini , Josieli Loise de Queiros Silva; Barboza , Irany Aparecida Ferreira da Cunha; Souza, Aracelly De Oliveira Franco; Bernhardt, Cristiane Otilia Colossi (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf